8.3 5 Please solve. Thanks!

label Algebra
account_circle Unassigned
schedule 1 Day
account_balance_wallet $5

May 4th, 2015

solve for x

(x*x*(-4)) + (6*0*4) + (2*6*5) - ((2*x*4) + (6*6*-4) + (x*0*5)) = 204

-4x^2 + 0 + 60 - (8x - 144 + 0) = 204

-4x^2 - 8x + 204 - 204 = 0

-4x^2 - 8x = 0

-4x(x - 2) = 0

-4x = 0  and x - 2 = 0

x = 0 and x = 2 

x = 0,2 - answer


May 4th, 2015

Did you know? You can earn $20 for every friend you invite to Studypool!
Click here to
Refer a Friend
...
May 4th, 2015
...
May 4th, 2015
Oct 21st, 2017
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer